Sugarcane cultivar selection for ethanol production using dilute acid pretreatment, enzymatic hydrolysis and fermentation - Benjamin, Yuda L. (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.